(3hKGFb ecjI (B(1044 (3g`(B-1375 (3g`(B) /s - (3ecGhj, MSGe Hf YHO GdYRjRs ((3GdQjGV (B:s (3eQcR JGQjN ecI GdecQeI ,s, 2016)
(3gPG GdcJGH jSJYQV hKGFb eJUdI HJGQjN ecI GdecQeI, JJfhY ehVhYGJgG Hjf ChbGa hhKGFb Jedc hMUQ JQcGJ hOYGhj bVGFjI hYbhO EjLGQ hhUGjG haQeGfGJ SdWGfjI hZjQgG, ebOeG OQGSI dgPg GdhKGFb eY JhVjM eUGOQgG hJGQjN cJGHJgG(B. (3hjMGhd gPG GdcJGH ef NdGd GSJYQGV gPg GdhKGFb GSJceGd LRA ef JGQjN ecI GdecQeI hNUhUG aj eLGd GdMjGI GdGLJeGYjI hGdGbJUGOjI hGdOjfjI, MjK jhVM echfGJ GdHjJ Gdecj heMJhjGJg hCSeGA edGHS GdQLGd hGdfSGA aj ecI Edi LGfH GdJhKjb GdJGQjN ddeUWdMGJ GdMVGQjI aj eQGMd JGQjNjI eNJdaI ceG jbOe JhKjbG ddefTCJ GdYeQGfjI aj ecI hhMOGJgG GdechfI dgG(B.s
(3jTJed Ydi cTGa(B.s
(3HHdjhLQGajI (B: (3UaMI (B556-581.s
Keywords: (3GdhKGFbs -- (3ecI GdecQeIs -- (3JGQjNs; (3ecI GdecQeIs -- (3JGQjNs -- (3eUGOQs